Reinforced behavioral variability in the valproate rat model of autism spectrum disorder. Issue 3 (25th April 2022) - Galizio, Ann; Odum, Amy L.
Abstract : Individuals diagnosed with autism spectrum disorder (ASD) tend to display restricted, repetitive behaviors and deficits in social interaction. Rats exposed to valproate (VPA) in utero have been shown to model symptoms of ASD. In previous research, VPA rats engaged in less social interaction and more repetitive responding than controls. The purpose of the present study was to further investigate behavioral variability in the VPA rat model of ASD by testing VPA and control rats in a reinforced‐behavioral‐variability operant task. In this procedure, rats emitted sequences of lever presses, some of which produced food. During baseline, food was delivered probabilistically, and variability was not required. Next, rats were exposed either to a variability contingency, in which food was only delivered following sequences that differed sufficiently from previous sequences (i.e., variability required), or to a yoked contingency, in which variability was not required. We hypothesized that VPA rats would behave less variably than controls in this task. However, VPA and control rats responded similarly variably when variability was required. Furthermore, VPA rats behaved slightly more variably than controls during baseline and yoked conditions, when variability was not required. These findings contribute to the complex literature surrounding the VPA rat model of ASD.